Is sub-national healthcare social protection sufficient for protecting rare disease patients? the case of China - Xu, Juan; Yu, Mingren; Zhang, Zhiguo; Gong, Shiwei; Li, Bingqin (Frontiers in Public Health, 2023)
Background: Failing to provide social support to cover healthcare costs for rare diseases would lead to great financial distress for the patients and their families. People from countries without a well-developed health safety-net are particularly vulnerable. Existing literature on rare diseases in China focuses on the unmet care needs of the patients and the difficulties of caregivers and physicians. Few study examines the state of social safety net, the unresolved issues and whether the current localized arrangements are sufficient. This study aimed to gain in depth knowledge of the current policy system and make sense of the local varieties, which would be essential for developing strategies for future policy changes. Methods: This systematic policy review focused on the provincial level policies on subsidizing the healthcare costs for people with rare diseases in China. The cut off point for the policies was March 19, 2022. The researchers coded the healthcare cost reimbursement policies and identified the different provincial level models based on the usage of reimbursement components. Results: 257 documents were collected. Five provincial level models (Process I, II, III, IV and V) have been identified with the five components across the country: Basic Medical Insurance for Outpatient Special Diseases (OSD), Catastrophic Medical Insurance for Rare Diseases (CMIRD), Medical Assistance for Rare Diseases (MARD), Special Fund for Rare Diseases (SFRD) and Mutual Medical Fund (MMF). The local health safety-net in each region is a combination of one or more of the five processes. Regions vary greatly in their rare diseases coverage and reimbursement policies. Conclusions: In China, the provincial health authorities have developed some level of social protection for rare disease patients. However, there are still gaps regarding coverage and regional inequality and there is room for a more integrated healthcare safety-net for people suffering from rare diseases at the national level.